2022
DOI: 10.3389/fcell.2021.806850
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Specific Protease 25 Aggravates Acute Pancreatitis and Acute Pancreatitis-Related Multiple Organ Injury by Destroying Tight Junctions Through Activation of The STAT3 Pathway

Abstract: Ubiquitin-specific protease 25 (USP25) plays an important role in inflammation and immunity. However, the role of USP25 in acute pancreatitis (AP) is still unclear. To evaluate the role of USP25 in AP, we conducted research on clinical AP patients, USP25wild-type(WT)/USP25 knockout (USP25−/−) mice, and pancreatic acinar cells. Our results showed that serum USP25 concentration was higher in AP patients than in healthy controls and was positively correlated with disease severity. AP patients’ serum USP25 levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…1D). Another study has shown that USP25 is prominently expressed in AP (15), but the underlying role of USP25 in pyroptosis of acinar cells in AP remains unclear. The expression levels of USP25 in AP cell models were examined, and it was found that the treatment of LPS and CRE notably upregulated USP25 expression levels ( P < 0.01, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1D). Another study has shown that USP25 is prominently expressed in AP (15), but the underlying role of USP25 in pyroptosis of acinar cells in AP remains unclear. The expression levels of USP25 in AP cell models were examined, and it was found that the treatment of LPS and CRE notably upregulated USP25 expression levels ( P < 0.01, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, USP25 knockdown blocks the activation of NF-κB and the production of proinflammatory cytokines in cells infected with RNA virus (45), and the activation of NF-κB is known to maintain inflammation and acinar injury in AP (46). USP25 propels the progression of AP in CRE-treated mice via activating the STAT3 pathway, and Stat3 binding to the NLRP3 promoter exacerbates NLRP3/ caspase-1-mediated pyroptosis of neurons in mice with epilepsy (15,47). Altogether, the above evidence indicated the alleviative role of silencing USP25 in pyroptosis of acinar cells treated with LPS and CRE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT pathway up-regulation inflammation (32,33) resulting in persistent and intensified inflammation (26). TLR9 is expressed in resident immune cells of the pancreas, which are predominantly represented by macrophages, and it is an important DAMP receptors upstream of inflammasome activation, and caspase-1, and NLRP3 inflammasome are required for the development of inflammation in AP (20,27).…”
Section: The Mechanism Of Acute Pancreatitismentioning
confidence: 99%
“…4 The death of intestinal epithelial cells (IECs) and the disruption of TJs are important causes of intestinal barrier dysfunction. 5 TJs are complex, highly dynamic structures composed of a variety of transmembrane proteins, often located between two adjacent cells at the apical tip of the epithelium, thus sealing the intercellular space, limiting the penetration of toxic molecules within the cavity while allowing the absorption of nutrients and moisture. 6 Once the TJ is damaged, this protective mechanism is disrupted, allowing toxins and bacteria from the gut to transfer to the abdominal cavity or other body organs, resulting in a series of symptoms such as bloody diarrhea, bacterial migration, and even sepsis, which can have serious consequences.…”
mentioning
confidence: 99%